Analisis Dynamic Capabilities Dan Entrepreneurial Orientation Terhadap Competitive Advantage (Survey Pada Home Industry Sektor Kuliner Dengan Rating Google Maps 4 Ke Atas Di Kota Sukabumi) - Dian Rahma Putri; Kokom Komariah; Sopyan Saori (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to determine the Analysis of Dynamic Capabilities and Entrepreneurial Orientation on Competitive Advantage. The research method used is quantitative method with descriptive and associative approaches. The sampling technique in this study used non probability sampling with saturated sample method with a sample size of 36 Home Industry Culinary Sector businesses with Google Maps Rating 4 upwards in Sukabumi City as respondents. The data analysis technique used in this study is multiple linear regression. The research results based on the simultaneous test (F test) show that dynamic capabilities and entrepreneurial orientation have a simultaneous influence on competitive advantage. The results of the hypothesis test (T test) show that entrepreneurial orientation has no effect on competitive advantage, while dynamic capabilities have a significant effect on competitive advantage in the culinary sector home industry with a google maps rating of 4 and above in Sukabumi City.